Analisis dan Identifikasi Sisa Material Konstruksi pada Pekerjaan Beton (Studi Kasus pada pekerjaan Pembangunan Pasar Rakyat Talang Banjar) - Elvira Handayani; Fenel Veronata (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
In the implementation of a building construction project, it cannot be avoided the emergence of the remaining construction material or called construction waste. The rest of the material is something that is of the nature more than what is required either in the form of work or construction material that is left / scattered / damaged so that it cannot be used again according to its function. The amount of residual material can be minimized by exploring the factors that cause the residual material to occur and the use of a good management system. The more residual material found on the project, it can be interpreted that the smaller the profit from implementing the project.